2018
DOI: 10.1007/s10508-018-1239-y
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Relations Between Self-Reported Gender Identity and Sexual Orientation in an Online Sample of Cisgender Individuals

Abstract: The present study explored the relations between self-reported aspects of gender identity and sexual orientation in an online sample of 4756 cisgender English-speaking participants (1129 men) using the Multi-Gender Identity Questionnaire and a sexual orientation questionnaire. Participants also labeled their sexual orientation. We found a wide range of gender experiences in the sample, with 38% of the participants feeling also as the “other” gender, 39% wishing they were the “other” gender, and 35% wishing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 92 publications
3
15
0
Order By: Relevance
“…All participants, regardless of gender identity, indicate to what extent they feel like a woman and feel like a man; to what extent they wish to be a woman and a man, etc. Results from large non-clinical samples indicate that humanity does not consist of 'typical women' and 'typical men'; instead, there was a large diversity of responses in gender identification and expression, regardless of gender identity (Jacobson & Joel, 2018;Joel et al, 2014).…”
Section: Multi-gender Identity Questionnairementioning
confidence: 97%
“…All participants, regardless of gender identity, indicate to what extent they feel like a woman and feel like a man; to what extent they wish to be a woman and a man, etc. Results from large non-clinical samples indicate that humanity does not consist of 'typical women' and 'typical men'; instead, there was a large diversity of responses in gender identification and expression, regardless of gender identity (Jacobson & Joel, 2018;Joel et al, 2014).…”
Section: Multi-gender Identity Questionnairementioning
confidence: 97%
“…'Normative' 1 in this literature refers to people who feel that their assigned birth sex is aligned with their affirmed gender identity, and who generally conform to heterosexual norms, or people who are not plurisexual (i.e., are sexually attracted by only one sex). Joel and colleagues explored identity using a questionnaire which measured gender identity, gender dysphoria, and gender performance (Multi-GIQ questionnaire; Joel et al, 2014; see also Jacobson & Joel, 2018 among people who identified as women, men, and queer. They found that, among self-identified women and men, over 35% of people reported feeling the 'opposite' gender, both genders, or neither.…”
Section: I S G E N D E R a N Abstract C O N C E P T ?mentioning
confidence: 99%
“…The two studies also challenged the common assumption that an atypical sexuality predicts an atypical gender identity by showing that the observed variability in gender identity in cisgender individuals was only weakly related to sexual attraction and to self-labeled sexual orientation (Jacobson & Joel, 2018;Joel et al, 2013).…”
mentioning
confidence: 96%
“…In two recent studies we have shown that gender identities that transcend the either/or (i.e., either a man or a woman) conceptualization are also present among cisgender individuals (i.e., individuals whose self-labeling is the same as their birthassigned category). Using the Multi-gender Identity Questionnaire (Multi-GIQ; Jacobson & Joel, 2018;Joel, Tarrasch, Berman, Mukamel, & Ziv, 2013) we found that cisgender participants presented a range of gender identity experiences with different levels of feeling as the "other" gender, wishing to be the "other" gender, and/or wishing to have the body of the "other" sex (Jacobson & Joel, 2018;Joel et al, 2013). In other words, feelings and wishes that are usually considered typical of individuals with transgender or nonbinary identity labels were also present in cisgender individuals (for a similar finding in children, see Martin, Andrews, England, Zosuls, & Ruble, 2017).…”
mentioning
confidence: 99%